Child Neurology: Pathologically Confirmed Thrombotic Microangiopathy Caused by Onasemnogene Abeparvovec Treatment for SMA. (10th May 2022) - Yazaki, Kotaro; Sakuma, Satoru; Hikita, Norikatsu; Fujimaru, Rika; Hamazaki, Takashi
Abstract : Onasemnogene abeparvovec is an adeno-associated virus vector-based gene therapy for spinal muscular atrophy (SMA). Although several cases of drug-induced thrombotic microangiopathy due to onasemnogene abeparvovec have been reported, none has been confirmed pathologically. Here, we present renal histopathologic findings of TMA due to onasemnogene abeparvovec. On day 5 after receiving onasemnogene abeparvovec, a 23-month-old girl with SMA type 1 developed thrombocytopenia, microangiopathic hemolytic anemia, liver dysfunction, acute kidney injury, and hypertension. She was diagnosed with TMA and received an increased dose of prednisolone, antihypertensives, diuretics, packed red blood cell and platelet transfusion, a single dose of eculizumab, 4 cycles of plasmapheresis, and intermittent and continuous hemodialysis. Her TMA resolved by day 30. On day 49, renal biopsy was performed. Light microscopy revealed proliferation of glomerular mesangial cells and matrix, with mesangiolysis, endothelial cell swelling, and partial double contours of the glomerular basement membrane. Electron microscopy showed endothelial injury, with edematous changes of the subendothelial spaces and neoformation of the basement membrane, without electron-dense depositions. These findings are compatible with the recovery phase of TMA. One year after drug administration, her motor function is improved. She can hold her posture against gravity and has neither dysphagia nor respiratory disturbance, but mild hypertension persists. Physicians should be vigilant regarding TMA as a severe side effect of onasemnogene abeparvovec treatment, especially when thrombocytopenia, hemolytic anemia, increased lactate dehydrogenase, or acute kidney injury is present.